Update on wide- and ultra-widefield retinal imaging - Shoughy, Samir S (Indian J Ophthalmol, 2015)
The peripheral retina is the site of pathology in many ocular diseases and ultra-widefield (UWF) imaging is one of the new technologies available to ophthalmologists to manage some of these diseases. Currently, there are several imaging systems used in practice for the purpose of diagnostic, monitoring disease progression or response to therapy, and telemedicine. These include modalities for both adults and pediatric patients. The current systems are capable of producing wide- and UWF color fundus photographs, fluorescein and indocyanine green angiograms, and autofluorescence images. Using this technology, important clinical observations have been made in diseases such as diabetic retinopathy, uveitides, retinal vascular occlusions and tumors, intraocular tumors, retinopathy of prematurity, and age-related macular degeneration. Widefield imaging offers excellent postoperative documentation of retinal detachment surgery. New applications will soon be available to integrate this technology into large volume routine clinical practice.